Continuous Subcutaneous Insulin Infusion Placement in Preschool Children Newly Diagnosed with Type 1 Diabetes - Teixeira, Liliana (2023)
Introduction: The incidence of childhood type 1 diabetes is increasing worldwide, especially in young children. According to international guidelines, continuous subcutaneous insulin infusion is the preferred method of insulin delivery for preschool children. This study aimed to evaluate the efficacy and safety of continuous subcutaneous insulin infusion treatment soon after diagnosis in preschool children with type 1 diabetes. Methods: A retrospective study was performed from 2016 to 2019, including all preschool children who placed continuous subcutaneous insulin infusion system up to two months after the diagnosis of type 1 diabetes. These patients were followed up for 18 months. Results: This study included 11 patients (median age of 2.55 years at diagnosis, 54.5% females). All patients had a low C-peptide at diagnosis with a median of 0.45 ng/mL (interquartile range 0.18-0.58 ng/mL). The median of hemoglobin A1c decreased from 9.5% (interquartile range 8.1%-10.4%) at diagnosis to 7.4% (interquartile range 7.1%-7.7%) after 18 months of follow-up. The median of the total daily insulin dose increased from 0.49 IU/kg/day (interquartile range 0.45-0.49 IU/kg/ day) to 0.70 IU/kg/day (interquartile range 0.61-0.78 IU/kg/day). Based on glucometer records, the median of self-monitoring blood glucose varied between 6.15-7.95 measures per day. The mean ± standard deviation of glucose varied between 158.5 ± 68.5 and 186 ± 83 mg/dL. The median value of the coefficient of variation varied between 42.5%- 47.9%. During the 18-month follow-up, no patient experienced diabetic ketoacidosis, severe hypoglycemia, or local complications. Conclusion: The continuous subcutaneous insulin infusion seems safe and effective as an initial therapeutic approach to type 1 diabetes in preschool-aged children.